Sivan Hirsch-Hoefler and Cass Mudde (2020), The Israeli Settler Movement: Assessing and Explaining Social Movement Success. New York: Cambridge University Press - Stagni, Federica (PARTECIPAZIONE E CONFLITTO, 2021)
For Book Reviews Abstract is not required